The Effect of the EGFR - Targeting Compound 3-[(4-Phenylpyrimidin-2-yl) Amino] Benzene-1-Sulfonamide (13f) against Cholangiocarcinoma Cell Lines - Papavee Samatiwat; Lueacha Tabtimmai; Prapasiri Suphakun; Nattanan Jiwacharoenchai; Borvorrnvat Toviwek; Veerapol Kukongviriyapan; M. Paul Gleeson; Kiattawee Choowongkomon (My University, 2021)
Objective: Cholangiocarcinoma (CCA) is a noxious malignancy of epithelium of the bile duct with a low response rate to chemotherapy. The epidermal growth factor receptor (EGFR) signaling pathway is implicated in the development of cancerous cells, especially CCA. In this study, we report detailed biological profiling of 13f identified from our earlier hit expansion studies. The aim of this work was to expand our understanding of 13f via more detailed investigations of its mechanism of action against KKU-100, KKU-452 and KKU-M156 CCA cells, as well as in comparison to the EGFR inhibitor Gefitinib and non-specific chemotherapeutic agents such as Cisplatin. Methods: Inhibiting EGFR-Kinase, cytotoxicity, clonogenic assay, wound healing and apoptosis were performed. Levels of total expression of EGFR and EGFR phosphorylation proteins were detected. Results: 13f was confirmed as an inhibitor of EGFR with an IC50 value against the tyrosine kinase of EGFR of 22 nM and IC50 values for 48 h incubation period were 1.3 ± 1.9, 1.5 ± 0.4 and 1.7 ± 1.1 µM of KKU-100, KKU-452 and KKU-M156, respectively through dose- and time-dependent induction of early apoptosis of CCA cells. The compound also suppressed the clonogenic ability of KKU-100 and KKU-M156 cells stronger than Gefitinib, while potently inhibiting EGF-stimulated CCA cell migratory activity in KKU-452 cells. It was observed that under normal conditions EGFR was activated in CCA cells. EGF-stimulated basal expression of EGFR in KKU-452 cells was suppressed following 13f treatment, which was significantly greater than that of the marketed EGFR inhibitor Gefitinib. Conclusion: In summary, our study showed that 13f has potent anti-cancer activities including antiproliferation, clonogenic ability and migration through the modulation of EGFR signaling pathway in CCA for the first time. The compound represents an interesting starting point as a potential chemotherapeutic agent in ongoing efforts to improve response rate in CCA patients.
Keywords: Clonogenic assay; EGFR Inhibitors; Cholangiocarcinoma and Gallbladder Cancer Studies